Solar UV-B radiation affects leaf quality and insect herbivory in the southern beech tree Nothofagus antarctica - Rousseaux, Maria Cecilia; Julkunen Tiitto, Riitta; Searles, Peter Stoughton; Scopel, Ana Leonor; Aphalo, Pedro J.; Ballare, Carlos Luis (Oecologia)
We examined the effects of solar ultraviolet-B (UV-B) radiation on plant-insect interactions in Tierra del Fuego (55°S), Argentina, an area strongly affected by ozone depletion because of its proximity to Antarctica. Solar UV-B under Nothofagus antarctica branches was manipulated using a polyester plastic film to attenuate UV-B (uvb-) and an Aclar film to provide near-ambient UV-B (uvb+). The plastic films were placed on both north-facing (i.e., high solar radiation in the Southern Hemisphere) and south-facing branches. Insects consumed 40% less leaf area from north- than from south-facing branches, and at least 30% less area from uvb+ branches than from uvb-branches. The reduced herbivory on leaves from uvb+ branches occurred for both branch orientations. Leaf mass per area increased and relative water content decreased on north- versus south-facing branches, while no differences were apparent between the UV-B treatments. Solar UV-B did lead to lower gallic acid concentration and higher flavonoid aglycone concentration in uvb+ leaves relative to uvb- leaves. Both the flavonoid aglycone and quercetin-3- arabinopyranoside were higher on north-facing branches. In laboratory preference experiments, larvae of the dominant insect in the natural community, Geometridae "Brown" (Lepidoptera), consumed less area from field-grown uvb+ leaves than from uvb- leaves in 1996-97, but not in 1997-98. Correlation analyses suggested that the reduction in insect herbivory in the field under solar UV-B may be mediated in part by the UV-B effects on gallic acid and flavonoid aglycone. Fil: Rousseaux, Maria Cecilia. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Instituto de Investigaciones Fisiológicas y Ecológicas Vinculadas a la Agricultura. Universidad de Buenos Aires. Facultad de Agronomía. Instituto de Investigaciones Fisiológicas y Ecológicas Vinculadas a la Agricultura; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro ...